Eternal travel toolkit / Dani Asmadi Ibrahim ... [et al.] - Ibrahim, Dani Asmadi; Jamali, Amal Hayati; Zuber, Zakiah; Mohd Daud, Ahmad Nasir (2020)
Funeral Management is a fardhu kifayah demand from every Muslim to other Muslims. There is a lot of theoretical and practical learning either at the school level, higher education level or at the surau or mosque level to give understanding to the community the importance of funeral management knowledge. However there are still many who will panic or do not know what to do in the event of death in their place. Thus, in line with the increasingly advanced technological advances, we took the initiative to develop customer-friendly applications by using mobile android phones, steps that need to be implemented in the funeral management process. The user simply presses the option button provided to know the process from start to finish of the funeral management perfectly. This application is integrated with interactive multimedia such as text, video, audio and illustrations to attract interest and improve user understanding. The innovation produced saves cost and time for users in perfecting funeral management.